Latinas narratives of domestic abuse : discrepant versions of violence - Trinch, Shonna L. (Impact, studies in language and society, 2003)
In the American legal system valid witness-testimony is supposed to be invariable and unchanging, so defense attorneys highlight seeming inconsistencies in victims' accounts to impeach their credibility. This book offers an examination of how and why victims of domestic violence might seem to be 'changing their stories, ' in the criminal justice system, which may leave them vulnerable to attack and criticism. Latinas' Narratives of Domestic Abuse: Discrepant versions of violence investigates the discourse of protective order interviews, where women apply for court injunctions to keep abusers aw.